EVALUASI UJI KETURUNAN PULAI DARAT (Alstonia angustiloba Miq.) UMUR TIGA TAHUN DI WONOGIRI, JAWA TENGAH - Mashudi Mashudi; Mudji Susanto (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2016)
Evaluation were observed at three years old of Alstonia angustiloba Miq. progeny trial at Wonogiri, Central Java. The experimental design of the trial was laid out in Randomized Complete Block Design consisting of 43 families, 6 replications, 4 tree-plot and spacing of 3 x 3 meters. This study was aimed to observe the adaptability, the growth variation (height, stem diameter and stem volume) and the estimates of heritability, genetic correlation and phenotipic correlation among the three growth traits.The results of study showed that the adaptability was not significantly different between populations and families with survival rate at 80.04 ± 25.34%. Analysis of variance showed that population and families were significantly different for height, stem diameter and stem volume. Pendopo, Carita, and Lubuk Linggau were the best populations in height growth (3.12 – 3.4 m) and stem diameter (4.07 – 4.65 cm). Pendopo population was the best population in stem volume (0.0047 m3). The estimates of individual heritabilities were around 0.32; 0.20, and 0.13 for height, stem diameter and stem volume, respectively. While the family heritabilities were around 0.59; 0.49, and 0.42 for height, stem diameter and stem volume, respectively. Genetic and phenotipic correlation among the three traits were positive and strong at 0.96 and 0.86 for height and diameter, 0.92 and 0.80 for height and stem volume then 0.89 and 0.95 for diameter and stem volume.